Taxing Expats. A Study in Instrumental versus Expressive Voting - Charles B. Blankart; Simon Margraf (Verein für Socialpolitik, 2010)
A fundamental question in public choice is: How do people vote? According to the preferred outcome (instrumentally) or according to principles (expressively)? The theoretical discussion eventually led to the hypothesis that voters vote non-strategically according to their preferences, as the probability of owning the marginal vote and in turn determining the outcome with a large number of voters is very low. If we add that they weigh their preferences with the impact that the political outcome has on their economic well-being, we come to the conclusion that if the latter is high, they vote instrumentally, if it is low, they are likely to vote expressively. A unique data set on a natural experiment in Switzerland allows us to test this hypothesis. Citizens of the canton of Zurich voted in 2009 on the highly controversial issue whether to tax non-working and hence mobile foreign residents at a special preferential tax base in order to attract them instrumentally as tax payers or to tax all persons at the same base according to general tax principles. Overall, 53% of the voters preferred to abolish preferential taxation of expats. Our econometric analysis reveals that in rural communities, where attracting rich expats has a sensible impact on communities' budget, citizens voted instrumentally, whereas in large cities where the budgetary impact is small, voters voted expressively. This outcome raises a more fundamental question on the design of the democracy. It cannot be overlooked that the two groups voted on two different issues. Rural voter's choice was marginal in the sense that they asked: Should we partly give up our tax principles to obtain additional revenues? Their answer was yes. Urban voters, who expected no sensible revenue effect from the tax privileges, in contrast, asked themselves: Should we give up tax privileges for merely marginal or even no benefits? Their answer was no! But if so why should the urban voters in their situation impose their own values on rural voters whose situation is different? This dilemma could be overcome if urban and rural voters voted separately under a decentralized more "federalistic" design of their government.
Keywords: D78; H24; H71; 330; Voting; taxation